2018
DOI: 10.1038/s41380-018-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin recruitment to dopamine D2 receptor mediates locomotion but not incentive motivation

Abstract: The dopamine (DA) D2 receptor (D2R) is an important target for the treatment of neuropsychiatric disorders such as schizophrenia and Parkinson's disease. However, the development of improved therapeutic strategies has been hampered by our incomplete understanding of this receptor's downstream signaling processes in vivo and how these relate to the desired and undesired effects of drugs. D2R is a G protein-coupled receptor (GPCR) that activates G protein-dependent as well as non-canonical arrestin-dependent sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 82 publications
(104 reference statements)
7
60
0
Order By: Relevance
“…PAC1-hop1 was also shown to regulate Ca 2+ mobilization and neurosecretion 4346 . Such differential signal transduction could affect behavioral phenotypes, as previously demonstrated for other GPCRs 4750 . Accordingly, we have previously shown in adult mice that acute foot-shock stressor induces a change in the ratio between PAC1-hop and PAC1-null splice isoforms in the hypothalamic paraventricular nucleus 4 .…”
Section: Discussionsupporting
confidence: 55%
“…PAC1-hop1 was also shown to regulate Ca 2+ mobilization and neurosecretion 4346 . Such differential signal transduction could affect behavioral phenotypes, as previously demonstrated for other GPCRs 4750 . Accordingly, we have previously shown in adult mice that acute foot-shock stressor induces a change in the ratio between PAC1-hop and PAC1-null splice isoforms in the hypothalamic paraventricular nucleus 4 .…”
Section: Discussionsupporting
confidence: 55%
“…D2R upregulation in iSPNs enhances this modulation by dopamine and D2R-OENAcInd mice show 48 decreased baseline synaptic transmission as well as an enhancement in inhibition of synaptic transmission by 49 after activation of D2R with an agonist (Gallo et al, 2018). This could be measured via slice physiology at intra-50 striatal collaterals to the direct pathway and the canonical projections to the ventral pallidum (Gallo et al, 2018). 51 A follow up in vivo physiological analysis showed that the effects of disinhibition in D2R-OENAcInd mice are mostly 52 measurable at the level of the striato-pallidal synapse (Gallo et al, 2018).…”
Section: Introduction: 29mentioning
confidence: 99%
“…Pharmacological studies have uncovered an important role for 31 dopamine receptors in the Nucleus accumbens (NAc) in the regulation of incentive motivation and the willingness 32 to work for reward (Aberman, Ward, & Salamone, 1998;Berridge, 2007;Salamone, Correa, Farrar, & Mingote, 33 2007). In this context dopamine is thought to regulate effort-related processes that are important to overcome 34 work-related response costs rather than to adapt the animals response to changes in reward value (Filla et (iSPNs) projection neurons (D2R-OENAcInd mice) is sufficient to enhance motivation, whereas upregulation in 41 cholinergic interneurons (D2R-OEChAT mice), which also express D2Rs had no effect on progressive ratio 42 performance (Gallo et al, 2018) (Note, that for simplicity we are using the term indirect pathway, which may 43 have its limitations in the (Kupchik et al, 2015). 44…”
Section: Introduction: 29mentioning
confidence: 99%
See 1 more Smart Citation
“…At the μ-opioid receptor G protein signaling has been proposed to be responsible for analgesia, with side effects such as respiratory depression resulting from arrestin-mediated signaling (2,3), although this paradigm has recently been challenged (4)(5)(6). We have demonstrated that β-arrestin recruitment to the dopamine D2 receptor in indirect pathway neurons in the ventral striatum leads to enhanced locomotion, whereas G protein signaling is necessary for incentive behavior (7), further emphasizing the potential importance of biased signaling in more targeted therapeutics.…”
Section: Introductionmentioning
confidence: 90%